.25(60+16s)=.33(45+12s)

Simple and best practice solution for .25(60+16s)=.33(45+12s) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .25(60+16s)=.33(45+12s) equation:


Simplifying
0.25(60 + 16s) = 0.33(45 + 12s)
(60 * 0.25 + 16s * 0.25) = 0.33(45 + 12s)
(15 + 4s) = 0.33(45 + 12s)
15 + 4s = (45 * 0.33 + 12s * 0.33)
15 + 4s = (14.85 + 3.96s)

Solving
15 + 4s = 14.85 + 3.96s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-3.96s' to each side of the equation.
15 + 4s + -3.96s = 14.85 + 3.96s + -3.96s

Combine like terms: 4s + -3.96s = 0.04s
15 + 0.04s = 14.85 + 3.96s + -3.96s

Combine like terms: 3.96s + -3.96s = 0.00
15 + 0.04s = 14.85 + 0.00
15 + 0.04s = 14.85

Add '-15' to each side of the equation.
15 + -15 + 0.04s = 14.85 + -15

Combine like terms: 15 + -15 = 0
0 + 0.04s = 14.85 + -15
0.04s = 14.85 + -15

Combine like terms: 14.85 + -15 = -0.15
0.04s = -0.15

Divide each side by '0.04'.
s = -3.75

Simplifying
s = -3.75

See similar equations:

| 1+4a=-5+3a | | 5n-3=92 | | 5+4z-7=4z-2-z | | 3x-2=9-8x | | 576(72)=d | | x^4-7x^2+20=0 | | 5x+8=6x | | 2x+y-2z=-3 | | 1.6/24=n/60 | | 3y/8-2=4 | | 2v^2+7v+5= | | 4-5n=2-3n | | -4x+4-30-18x=.33 | | w^2+4w= | | 8k-=23-k-3k | | 5x-4=3n+2 | | K-5/6=-7 | | 2t=-13 | | 16s^2+24s+9= | | 3(2)+6(8+2)= | | B+10.8=12.80 | | 10=s/2+78 | | 1/3x=6-1/5x | | 3x+2(x+1)=6x+(3x-4) | | 7n-20=-48 | | c^2+14c+45= | | m^2+6m+4=-4 | | 4i(6+2i)= | | y=3.0x+1.7 | | 6x+3=12-2x | | t(5t+2)= | | 276/12 |

Equations solver categories